Portraits of japanese dance in Londrina, Paraná - Marani, Vitor Hugo; Camargo, Fernanda Marques Tresinari; Sborquia, Silvia Pavesi (Motrivivência, 2018)
This research sought to investigate the manifestations of Japanese dance in Londrina, Paraná, through the apprehension of this body culture through dialogue with different groups that are organized in the city. To do so, it used as a data collection procedure the documentary analysis - constituted by Japanese dance reports in the Folha de Londrina newspaper from 1980 to 2010 - and semi-structured interviews with coordinators of the mapped groups. The treatment of the data followed the analysis of thematic content, based on the transcriptions of the reports. The inference of the data allowed to conclude that the Japanese dance in the city of Londrina, in the state of Paraná, is structured in order to contribute to the permanence of the culture of Japanese immigrants and their families, and also to construct a culture of the colony that established itself Here adapted from the new cultural demands of contemporary society.